Three-dimensional printed cardiac fistulae: a case series. Issue 2 (4th May 2019) - Aroney, Nicholas; Markham, Ryan; Putrino, Anthony; Crowhurst, James; Wall, Douglas; Scalia, Gregory; Walters, Darren
Abstract: Background: Three-dimensional (3D) printing of cardiac fistulae allows for immediate understanding of their complex courses and anatomical relations. Models can be used to improve patient understanding, enhance the consenting process, facilitate communication between multidisciplinary staff at heart team meetings, and help plan surgical or percutaneous interventions. Case summary: We report four cases where 3D printed models were used as an adjunct with traditional measures in treating patients with complex cardiac fistulae. Discussion: In our cases, overall patient understanding was improved, staff at heart team meetings were more aware of anatomical anomalies and perioperatively planning saw adjustments made that may have ultimately benefited patient outcome. Our cases highlight the additional benefit that 3D printed models can play when treating patients with complex cardiac fistulae.